A new Frenguelliidae (Insecta: Odonata) from the early Eocene of Laguna del Hunco, Patagonia, Argentina - Petrulevičius, Julián F.; Nel, André (Zootaxa, 2013)
The discovery of a new specimen of Frenguelliidae, attributed to the new species Frenguellia Argentina, is noteworthy for the knowledge of the diversity within this little-known family.